If Integration Is the Keystone of Comprehension: Inferencing Is the Key. Issue 1 (2nd January 2021) - McNamara, Danielle S.
ABSTRACT: This article provides a commentary within the special issue, Integration: The Keystone of Comprehension. According to most contemporary frameworks, a driving force in comprehension is the reader's ability to generate the links among the words and sentences (ideas) in the texts and between the ideas in the text and what the readers already know. As such, the key to successful comprehension is generating inferences: inferences about what a word means, inferences to integrate ideas within the sentences, and inferences to integrate ideas within and outside the text. Accordingly, inferences provide the glue to hold it all together. While there is general agreement in this regard, the factors reported to be key to comprehension also depend on the focus of the research. Some studies focus on surface level and relatively brief measures of reading comprehension. These studies might conclude that comparable measures are the key to comprehension. Other studies use inference-level questions with a focus on comprehension and learning in the context of informational text, even multiple documents. These studies point toward the crucial importance of inference generation. The four articles in this special issue each tackle the question of how readers comprehend text from different angles, using different types of dependent measures, and with foci on different individual differences. Each of these studies provides a glimpse into different experimental paradigms used to investigate comprehension processes as well differing questions that are currently faced by discourse processes researchers.